Handheld Multifunctional Fluorescence Imager for Non-invasive Plant Phenotyping - Zhang, Ruochong; Koh, Sally Shuxian; Teo, Mark Ju Teng; Bi, Renzhe; Zhang, Shuyan; Dev, Kapil; Urano, Daisuke; Dinish, U. S.; Olivo, Malini (Frontiers in Plant Science, 2022)
Fluorescence imaging has shown great potential in noninvasive plant monitoring and analysis. However, current systems have several limitations such as bulky size, high cost, contact measurement and lack of multifunctionality, which may hinder its applications in wide range of settings including indoor vertical farming. Herein, we developed a compact handheld fluorescence imager enabling multipurpose plant phenotyping, including continuous photosynthetic activity monitoring and nondestructive anthocyanin quantification. The compact imager comprises of pulse-amplitude-modulated multi-color LEDs, optimized light illumination and collection, dedicated driver circuit board, miniaturized charge-coupled device camera and associated image analytics. Experiments conducted in drought stressed lettuce proved that the novel imager could quantitatively evaluate the plant stress by noninvasive measurement of photosynthetic activity efficiency. Moreover, noninvasive and fast quantification of anthocyanins in green and red Batavia lettuce leaves had excellent correlation (>84%) with conventional destructive biochemical analysis. Preliminary experimental results emphasize the high throughput monitoring capability and multifunctionality of our novel handheld fluorescence imager, indicating its tremendous potential in modern agriculture.